AGE ESTIMATION OF THIRD MOLAR IN SOUTH INDIAN POPULATION BY ABFO RECOMMENDED MINCER METHOD – AN INDIAN SPECIFIC FORMULA - Arumugam, Vidhya; Doggalli, Nagabhushana; Patil, Karthikeya (Journal of Forensic Medicine and Toxicology, 2020)
Background: Third molar, being the only tooth which mineralize and erupt between 14 to 22 years, may be a significant parameter in identifying the individual of adolescence to young adult. As criminal laws are different for juvenile and adult, it is authoritative to differentiate child and an adult especially, when documentation is not properly maintained. Objectives: To determine the applicability of Mincer method of dental age estimation through third molars in South Indian population using orthopantomogram. Methodology: The study was conducted on 400 OPG (200 males, 200 females) of the age groups 14-22 years. They were divided into 8 groups (50 in each age group). Which were taken with PROMAX digital Planmeca Machine. Staging of all four third molars were done using Mincer adapted Demirjian et al. (1973) mineralization stages A H. Statistical analysis was performed, Descriptive statistics were obtained by calculating the means, standard deviations, Regression formulas were obtained for calculating dental age from tooth developmental stages, Empirical probability and accuracy was checked. Results: Result showed a strong relation of age with development stages of third molar teeth. The standard deviation of mean of tooth development stages is ± 0.5 years of age. Conclusion: As shown in the multiple and stepwise regression analysis lower left third molar are not significantly contributing for predicting the age, hence the use of one maxillary third molar and mandibular right third molar provided a statistically significant improvement in predictive accuracy, From the above observation, the present study predicted ages are closure to the observed ages as compared to Prediction values obtained by using Mincer’s formulae.